A Review of the Segmental Diameter of the Healthy Human Spinal Cord - Frostell, Arvid; Hakim, Ramil; Thelin, Eric Peter; Mattsson, Per; Svensson, Mikael (Frontiers in Neurology, 2016)
Knowledge of the average size and variability of the human spinal cord can be of importance when treating pathological conditions in the spinal cord. Data on healthy human spinal cord morphometrics have been published for more than a century using different techniques of measurements, but unfortunately, comparison of results from different studies is difficult because of the different anatomical landmarks used as reference points along the craniocaudal axis for the measurements. The aim of this review was to compute population estimates of the transverse and anteroposterior diameter of the human spinal cord by comparing and combining previously published data on a normalized craniocaudal axis. We included eleven studies presenting measurements of spinal cord cross-sectional diameters, with a combined sample size ranging from 15 to 488 subjects, depending on spinal cord level. Based on five published studies presenting data on the lengths of the segments of the spinal cord and vertebral column, we calculated the relative positions of all spinal cord neuronal segments and vertebral bony segments and mapped measurements of spinal cord size to a normalized craniocaudal axis. This mapping resulted in better alignment between studies and allowed the calculation of weighted averages and standard deviations along the spinal cord. These weighted averages were smoothed using a generalized additive model to yield continuous population estimates for transverse and anteroposterior diameter and associated standard deviations. The spinal cord had the largest transverse diameter at spinal cord neuronal segment C5 (13.3 +/-2.2), decreased to segment T8 (8.3 +/-2.1), and increased slightly again to 9.4 +/-1.5 at L3. The anteroposterior diameter showed less variation in size along the spinal cord at C5 (7.4 +/- 1.6), T8 (6.3 +/- 2.0), and L3 (7.5 +/- 1.6). All estimates are presented in millimeters +/- 2 standard deviations. We conclude that segmental transverse and anteroposterior diameters of the healthy human spinal cord from different published sources can be combined on a normalized craniocaudal axis and yield meaningful population estimates. These estimates could be useful in routine management of patients with neurodegenerative diseases as well as for clinical research and experimental applications aimed at surgical spinal cord repair.